Bromodomain inhibition exerts its therapeutic potential in malignant pleural mesothelioma by promoting immunogenic cell death and changing the tumor immune-environment. (4th March 2018) - Riganti, Chiara; Lingua, Marcello Francesco; Salaroglio, Iris Chiara; Falcomatà, Chiara; Righi, Luisella; Morena, Deborah; Picca, Francesca; Oddo, Daniele; Kopecka, Joanna; Pradotto, Monica; Libener, Roberta; Orecchia, Sara; et al.
ABSTRACT: Systemic treatment of malignant pleural mesothelioma (MPM) is moderately active for the intrinsic pharmacological resistance of MPM cell and its ability to induce an immune suppressive environment. Here we showed that the expression of bromodomain (BRD) proteins BRD2, BRD4 and BRD9 was significantly higher in human primary MPM cells compared to normal mesothelial cells (HMC). Nanomolar concentrations of bromodomain inhibitors (BBIs) JQ1 or OTX015 impaired patient-derived MPM cell proliferation and induced cell-cycle arrest without affecting apoptosis. Importantly, BBIs primed MPM cells for immunogenic cell death, by increasing extracellular release of ATP and HMGB1, and by promoting membrane exposure of calreticulin and ERp57. Accordingly, BBIs activated dendritic cell (DC)-mediated phagocytosis and expansion of CD8 + T-lymphocyte clones endorsed with antitumor cytotoxic activity. BBIs reduced the expression of the immune checkpoint ligand PD-L1 in MPM cells; while both CD8 + and CD4 + T-lymphocytes co-cultured with JQ1-treated MPM cells decreased PD-1 expression, suggesting a disruption of the immune-suppressive PD-L1/PD-1 axis. Additionally, BBIs reduced the expansion of myeloid-derived suppressor cells (MDSC) induced by MPM cells. Finally, a preclinical model of MPM confirmed that the anti-tumor efficacy of JQ1 was largely due to its ability to restore an immune-active environment, by increasing intra-tumor DC and CD8 + T-lymphocytes, and decreasing MDSC. Thereby, we propose that, among novel drugs, BBIs should be investigated for MPM treatment for their combined activity on both tumor cells and surrounding immune-environment.